Efficacy and safety of 3‐month dosing regimen of degarelix in Japanese subjects with prostate cancer: A phase III study. Issue 6 (23rd May 2018) - Ozono, Seiichiro; Tsukamoto, Taiji; Naito, Seiji; Horie, Shigeo; Ohashi, Yasuo; Uemura, Hiroji; Yokomizo, Yumiko; Fukasawa, Satoshi; Kusuoka, Hidehito; Akazawa, Rio; Saito, Masako; Akaza, Hideyuki
Abstract : Non‐inferiority in the cumulative castration rate of the 3‐month formulation of degarelix compared with the 3‐month formulation of goserelin was evaluated in subjects with prostate cancer. A phase III, open‐label, parallel‐arm study was carried out. An initial dose of 240 mg degarelix or 3.6 mg goserelin was given s.c.; after day 28, a maintenance dose of 480 mg degarelix or 10.8 mg goserelin was given once every 84 days. Non‐inferiority in castration rate and safety of degarelix to goserelin were evaluated. The primary end‐point was the cumulative castration rate from day 28 to day 364 and the non‐inferiority margin was set to be 10%. A total of 234 subjects with prostate cancer were randomized to the degarelix group (n = 117) and the goserelin group (n = 117). The cumulative castration rate was 95.1% in the degarelix group and 100.0% in the goserelin group. As there were no events in the goserelin group, an additional analysis was carried out using 95% confidence intervals of the difference in the proportion of subjects with castration. Analyses indicated the non‐inferiority of the 3‐month formulation of degarelix to goserelin. Degarelix showed more rapid decreases in testosterone, luteinizing hormone, follicle stimulating hormone, and prostate‐specific antigen levels compared with goserelin. The most common adverse events in the degarelix group were injection site reactions. Non‐inferiority of the 3‐month formulation of degarelix to goserelin was shown for testosterone suppression. The 3‐month formulation of degarelix was also found to be tolerated as an androgen deprivation therapy for patients with prostate cancer. This trial was registered with ClinicalTrials.gov (identifier NCT01964170). Abstract : This manuscript reports a phase III, open‐label, parallel‐arm study to evaluate non‐inferiority in the cumulative castration rate of the 3‐month formulation of degarelix compared with the 3‐month formulation of goserelin. The results in combination with sub‐analysis demonstrated the non‐inferiority of the 3‐month formulation of degarelix to goserelin.